SAT-469 Vitals for the Prompt Recognition of Myxedema Crisis in a Critically Ill Patient - Funke, Katalina (J Endocr Soc, 2020)
Myxedema coma is a rare but life-threatening condition if not treated promptly. The time from initial presentation to diagnosis may be prolonged in patients with severe illness whose presenting features are common to myxedema crisis. A 94-year-old male admitted to the neuroscience intensive care unit for acute stroke monitoring after intra arterial thrombolysis was treated for myxedema three days after initial labs revealed severe hypothyroidism and a myxedema score greater than 60. A diagnostic scoring system for the diagnosis of myxedema coma gives points for the following to easily identify patients with high likelihood of decompensated state of extreme hypothyroidism. Given the potential for under recognition of myxedema crisis in severe illness the clinician must pay close attention to vital signs and have a high level of suspicion for myxedema crisis and low threshold for treatment if myxedema score indicates high likelihood despite concomitant critical illness